Mechanical performance of hybrid Ilizarov external fixator in comparison with Ilizarov circular external fixator - Yilmaz, E; Belhan, O; Karakurt, L; Arslan, N; Serin, E (Elsevier Sci Ltd, 2003)
Objective. The aim of this study was to determine the stiffness characteristics of the standard and hybrid Ilizarov fixators. Design. Five different frame models (one standard and four hybrid Ilizarov) were designed. Four full rings were used in the standard Ilizarov frame. Two rings were placed proximal and two rings were placed distal to the osteotomy line with two wires at 90degrees to each other on each ring. The distal tibial fixation of all the hybrid configurations and standard Ilizarov fixator were the same, and only the proximal fixations were different. In hybrid models, different numbers of 90degrees femoral arches (1-3) were fixed to the proximal segment by using the half-pins with different numbers (2-4) and different angles to each other (45degrees and 90degrees). Background. Numerous investigations have been performed to compare the mechanical properties of different frames. The Ilizarov method of fracture fixation and limb lengthening has recently gained international recognition. But its application is difficult in some anatomic localization, so that hybrid ring fixation frames of various configurations are gaining clinical popularity. Methods. Five different frame models were applied to the sheep tibial bones. The midpoint of the tibial bones was osteotomised and the osteotomy distracted for 2 cm. Four identical samples for each model were created and each identical sample of each model (n = 1) were tested four times in axial compression, antero-posterior and medio-lateral bending, and torsion. Results. In standard Ilizarov fixator, axial and bending stiffness was found to be more than all hybrid Ilizarov fixator models. Between the hybrid fixators, higher axial and bending stiffness was found when the number of femoral arches and half-pins were increased. Different angles between the half-pins formed 67% alteration in medio-lateral bending stiffness. No significant difference was found for torsional stiffness between the fixator models. Conclusions. For optimum fixator stiffness in hybrid fixators, at least three femoral arches and four half-pins Must be used and these half-pins should be placed at 90degrees angles and at different planes to each other. However, it should be remembered that, hybrid fixator models had less axial and bending stiffness than standard llizarov fixator model.
Keywords: hybrid Ilizarov external fixator; Ilizarov circular external fixator; biomechanics